Building Capacity For Preprint-Based Peer Review And Curation In Africa - Owango, Joy; Havemann, Jo (My University, 2020)
In Africa, only few stakeholders exist that have both the capacity and the pan-African scope to educate and build capacity about the opportunities and regionally applicable research publishing workflows that are available today. African researchers are often struggling with low salaries and high teaching demands, which is why it is difficult for them to serve as reviewers in assessing other researchers’ works. We therefore need to establish a culture and transparent and easy to follow workflow which is mutually beneficial not only for the recipient of a peer review, but also for the reviewer.
Keywords: peer review systems; Capacity Building; publishing workflows